Accurate In Vivo Nanothermometry through NIR‐II Lanthanide Luminescence Lifetime. Issue 48 (5th November 2020) - Tan, Meiling; Li, Feng; Cao, Ning; Li, Hui; Wang, Xin; Zhang, Chenyang; Jaque, Daniel; Chen, Guanying
Abstract: Luminescence nanothermometry is promising for noninvasive probing of temperature in biological microenvironment at nanometric spatial resolution. Yet, wavelength‐ and temperature‐dependent absorption and scattering of tissues distort measured spectral profile, rendering conventional luminescence nanothermometers (ratiometric, intensity, band shape, or spectral shift) problematic for in vivo temperature determination. Here, a class of lanthanide‐based nanothermometers, which are able to provide precise and reliable temperature readouts at varied tissue depths through NIR‐II luminescence lifetime, are described. To achieve this, an inert core/active shell/inert shell structure of tiny nanoparticles (size, 13.5 nm) is devised, in which thermosensitive lanthanide pairs (ytterbium and neodymium) are spatially confined in the thin middle shell (sodium yttrium fluoride, 1 nm), ensuring being homogenously close to the surrounding environment while protected by the outmost calcium fluoride shell (CaF2, ≈2.5 nm) that shields out bioactive milieu interferences. This ternary structure enables the nanothermometers to consistently resolve temperature changes at depths of up to 4 mm in biological tissues, having a high relative temperature sensitivity of 1.4–1.1% °C −1 in the physiological temperature range of 10–64 °C. These lifetime‐based thermosensitive nanoprobes allow for in vivo diagnosis of murine inflammation, mapping out the precise temperature distribution profile of nanoprobes‐interrogated area. Abstract : A class of NaYF4 @NaYF4 :Yb, Nd@CaF2 lifetime nanothermometers are developed with a high relative temperature sensitivity of 1.4% °C −1 in the physiological temperature range of 10–64 °C. These nanothermometers are able to map out the precise temperature distribution profile of nanoprobes‐interrogated area for in vivo diagnosis of murine inflammation.